P2P Lending's True Impact on the Money Supply: An ARDL Analysis of Inflation Volatility and Monetary Policy Response in Indonesia - Valentina, Dila; Aji, Tony Seno (Universitas Muhammadiyah Yogyakarta, 2026)
This study investigates the influence of peer-to-peer (P2P) lending, inflation, and the central bank interest rate (BI Rate) on Indonesia's broad money supply (M2) from 2019 to 2024. Utilizing the Autoregressive Distributed Lag (ARDL) model, the analysis confirms a stable, long-term cointegrating relationship among the variables. The significant and negative error correction term indicates a rapid adjustment process of the money supply back towards its long-run equilibrium following any short-term deviations. The findings reveal distinct temporal effects. In the short term, P2P lending has a significant positive impact on the money supply, highlighting its role as an immediate source of liquidity. Conversely, the BI Rate demonstrates a powerful and highly significant short-term influence. Inflation, meanwhile, shows a marginally negative effect in the short run. When examining the long-term dynamics, the positive effect of P2P lending becomes statistically insignificant, suggesting its influence may not permanently alter the equilibrium level of the money supply. These results strongly support the endogenous money theory, positing that financial innovations like P2P lending actively participate in the money creation process outside of traditional banking channels. The study concludes that to maintain financial system stability amid ongoing digital transformation, it is crucial for regulators to expand macroprudential supervision to encompass fintech activities. Furthermore, it recommends the integration of non-bank credit variables into the monetary policy framework to ensure a more comprehensive and effective approach.